Orally Effective Aminoalkyl 10H‐Indolo[3, 2‐b]quinoline‐11‐carboxamide Kills the Malaria Parasite by Inhibiting Host Hemoglobin Uptake. (13th November 2018) - Mudududdla, Ramesh; Mohanakrishnan, Dinesh; Bharate, Sonali S.; Vishwakarma, Ram A.; Sahal, Dinkar; Bharate, Sandip B.
Abstract: A series of indolo[3, 2‐ b ]quinoline‐C11‐carboxamides were synthesized by incorporation of aminoalkyl side chains into the core of indolo[3, 2‐ b ]quinoline‐C11‐carboxylic acid. Their in vitro antiplasmodial evaluation against Plasmodium falciparum led to the identification of a 2‐(piperidin‐1‐yl)ethanamine‐linked analogue {2‐bromo‐ N ‐[2‐(piperidin‐1‐yl)ethyl]‐10 H ‐indolo[3, 2‐ b ]quinoline‐11‐carboxamide (3 g )} (IC50 =1.3 μm ) as the most promising compound exhibiting good selectivity indices against mammalian cell lines. The kill kinetics on erythrocytic‐stage parasites revealed that3 g caused complete killing of only the trophozoite‐stage parasites. Mechanistic studies showed that3 g targets the food vacuole of the parasite and inhibits hemoglobin uptake, β‐hematin formation, and the basic endocytic processes of the parasite. Analogue3 g was found to be orally bioavailable, and its curative antimalarial studies at 50 mg per kg p.o. against a Plasmodium berghei (ANKA)‐infected mouse model revealed that mice treated with3 g showed 27–35 % suppression of parasitemia with an increase in life span relative to untreated, control mice. Thus, the present work demonstrated a proof of concept for the oral efficacy of indolo[3, 2‐ b ]quinoline‐C11‐carboxamides. Abstract : Bug out : The discovery of orally bioavailable compound3 g possessing promising in vitro and in vivo antimalarial activity is reported. Compound3 g targets the food vacuole of the parasite, inhibits the uptake of host hemoglobin, and also inhibits the basic endocytic processes of the parasite. In a Plasmodium berghei (ANKA)‐infected mouse model of malaria, mice treated with3 g show suppression of parasitemia and increased life span.